SYSTEMATIC LITERATURE REVIEW: EFEKTIVITAS MODEL EXPERIENTIAL LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SD - Annisa Hukma Shobiyya; Hani Fauziyah Syaiha; Rahayu Puji Lestari; Rasendriya Azaria; Zulpa Awaliyatul Padliyah; Hafiziani Eka Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this study is based on the low ability of elementary school students to connect mathematical concepts with real-life experiences in daily contexts. In addition, previous studies on the implementation of experience-oriented learning models have shown inconsistent findings. Therefore, this study aims to systematically review the effectiveness of the Experiential Learning model in improving elementary students' mathematical problem-solving skills. This study employed a Systematic Literature Review (SLR) method by identifying ten initial articles obtained from various national journal databases. These articles were then screened through four stages, namely initial data collection, preliminary analysis, selection or eligibility determination, and follow-up recommendations, based on topic relevance, alignment with research objectives, and methodological feasibility. From this process, three articles met all inclusion criteria and provided empirical evidence regarding the application of Experiential Learning in mathematics learning. The synthesis results indicate that the Experiential Learning model is effective in helping students understand problems, design solution strategies, and evaluate solutions reflectively through concrete experiences. In addition, this model also enhances student engagement, motivation, and independent learning in solving problems. However, limitations were found in teacher strategy variations, differences in student characteristics, and limited integration with digital media. Overall, the SLR results highlight the significant contribution of Experiential Learning to improving elementary students' mathematical problem-solving skills and recommend broader and more integrated implementation of this model.